Field report: The impact of socio-technical innovation bundles (STIB) on women and youth food security, empowerment and resilience in Ethiopia - Leul, Solomon Zewdu; Ketema, Dessalegn; Cosmas, Lutomia; Nchanji, Eileen (CGIAR Initiative on Gender Equality, 2024)
The Gender Equality Initiative (HER+) aims to conducts innovative gender and social science research by developing actionable solutions to enhance climate resilience, food security and empowerment of women in Africa. As one-sizef its-all solutions do not exist, HER+ with multiple stakeholders in the Veggies for Planet and People (V4P&P) project have co-designed diverse scenarios for bundling socio-technical innovations that increase income, build resilience, economic empowerment and food security for youth and women through Vegetable Business Networks (VBNs). We are working closely with the World Vegetable Center, the Netherlands Development Organisation (SNV) and Green Agro solutions by integrating social innovations (like the digitalization of market linkages, finance, nutrition and gender responsive trainings) into existing technological and technical innovations to increase adoption and benefits.